Union Bargaining and Intra-Industry Productivity Differentials: Theory and Evidence from Germany - Tobias Brändle; Florian Baumann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
This paper indicates that the extent of collective bargaining coverage in an industry may depend on the differences in firms productivity levels within the industry. Less pronounced differences in productivity levels make it easier to design collective wage contracts that are accepted by a wider range of firms within an industry. Higher dispersion in productivity levels gives rise to the use of firm-level wage agreements reached by unions, while coverage by industry-wide contracts is likely to decrease. We measure correlations between productivity variation and collective bargaining coverage in various industries using German linked-employer-employee data from 2000-2008 and find that the share of industry-wide collective bargaining agreements may indeed be negatively correlated with the dispersion of plant productivity within an industry, while the opposite might hold true for firm-level contracts.
Keywords: J51; D22; L16; 330